PENYELESAIAN SENGKETA RAHASIA DAGANG DI INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 30 TAHUN 2000 TENTANG RAHASIA DAGANG - Sherly Nelsa Fitri; Usawatun Hasanah (Al-Adl : Jurnal Hukum, 2023)
This study aims to find evidence on trade secret disputes and settling trade secret disputes in Indonesia. This research was conducted because there are many trade secret disputes in Indonesia at this time, and trade secrets have an essential role in the field of intellectual property rights, then trade secrets have the same important position as copyrights, trademarks, and designs. Global economic competition requires trade secret protection to create a healthy and dynamic economic environment. This legal research is included in normative legal research, which means research aimed at finding and formulating legal arguments through analysis of the subject matter. This research is perspective and applied, which means that this research is written according to law according to facts or legal events from the research results. Legal materials in this writing use primary legal materials and secondary legal materials. The legal materials were collected through document studies, law, and case approaches and then analyzed using deduction techniques. It can be seen that for proof if it is related to a license or the transfer of ownership rights to a trade secret if at any time a dispute occurs, then there is no authentic evidence or an authentic deed in writing made before a public official who is authorized to make it so that it will be difficult to prove when faced with evidence in a confidential case trade, settlement of trade secret disputes can be carried out by way of litigation or non-litigation. However, the legal subject of trade secrets is still unclear, so when a dispute occurs, longer evidence is needed to prove who owns the trade secret.